Huge Lymphangioma of the Esophagus Resected by Endoscopic Piecemeal Mucosal Resection - Dinghai Luo; Liping Ye; Weidan Wu; Haihong Zheng; Xinli Mao (Case Reports in Medicine)
We present an unusual case of a 41-year-old male patient with a large lymphangioma of the esophagus. Endoscopy revealed that the structure measured 60 × 10 mm in the mucosa and the submucosa and had a heterogenous echo pattern. The esophageal mass was successfully resected by endoscopic piecemeal mucosal resection. However, most esophageal lymphangiomas that are larger than 2 cm in diameter reported in the literature can be removed only through open surgery. Thus far, we know of no reported cases of endoscopic resection as a treatment for this case.